The use of the Neonatal Infant Pain Scale to assess pain in the Neonatal Intensive Care Unit: Integrative review of the literature (Research, Society and Development, 2023)
Newborns who are admitted to the ICU require specialized care, so the NIPS scale can be used by professionals to provide care to newborns. To identify the use of the Neonatal Infant Pain Scale to assess pain in the Neonatal Intensive Care Unit. The present study refers to an Integrative Literature Review (RIL) of a descriptive and exploratory nature with a qualitative approach. The search for information was carried out through the Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature, Analysis and Retrieval System Online (MEDLINE), Cochrane Central Register of Controlled Trials of the Cochrane Library and the Database of Nursing (BDENF) and Scientific Electronic Library Online (SCIELO). Emerged in two categories: pain in the newborn and the measures used to alleviate it; the use of the NIPS scale in newborn care. In the neonatal ICU, the smallest, undergoing several procedures, having a well-trained team is essential to alleviate the newborn's pain.